2011
DOI: 10.1186/1477-3155-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical potential of silver nanoparticles synthesized from calli cells of Citrullus colocynthis (L.) Schrad

Abstract: BackgroundAn increasingly common application is the use of silver nanoparticles for antimicrobial coatings, wound dressings, and biomedical devices. In this present investigation, we report, biomedical potential of silver nanopaticles synthesized from calli extract of Citrullus colocynthis on Human epidermoid larynx carcinoma (HEp -2) cell line.MethodsThe callus extract react with silver nitrate solution confirmed silver nanoparticles synthesis through the steady change of greenish colour to reddish brown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In agreement with the present finding, a work done by Satyavani and colleagues revealed that AgNPs induced cell death via activation of caspase-3 activity and DNA fragmentation which are both apoptotic events [42]. The increased level of caspase-3 activity was observed in human breast cancer cells MDA-MB-231 in response to the cytotoxic potential of the biologically synthesized AgNPs treatment [21].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the present finding, a work done by Satyavani and colleagues revealed that AgNPs induced cell death via activation of caspase-3 activity and DNA fragmentation which are both apoptotic events [42]. The increased level of caspase-3 activity was observed in human breast cancer cells MDA-MB-231 in response to the cytotoxic potential of the biologically synthesized AgNPs treatment [21].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current investigation are in accordance to previous studies (Raghunandan et al, 2011; that suggested that the peak from 1,607 to 1,636 cm −1 is due to C=C aromatic ring stretching vibrations. However, Satyavani et al (2011) proposed that the peaks at 1,620-1,636 cm −1 represent carbonyl group (C=O) present in polyphenols such as theaflavin, epicatechin gallate, and catechin gallate. The major sources for these vibration bands are various phytochemicals, flavonoids, and alkaloids that are copiously present in the leaf.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of colored solution was measured on the Multimode reader (Synergy HTX Multimode reader, BIOTEK, India) using a test wavelength of 490 nm (Freshney, 2010; Satyavani et al, 2011). Percentage toxicity was estimated for each concentration, and the IC 50 value was calculated for both nanoparticles (Freshney, 2005).…”
Section: Methodsmentioning
confidence: 99%